POSSIBILITIES OF INTRADUCTAL SANITATION OF SODIUM A HYPOCHLORITE IN THE COMPLEX TREATMENT OF ACUTE CHOLANGITIS - Шкурупій О. А. (World of Medicine and Biology, 2010)
During 2004 - 2008 years was maded bacteriological study of the bile, that got intraoperational or by endoscopy from 217 patients, which was operated on cause of cholelitial disease, choledoholitiasis and purulent cholangitis. From 169 patients bile for bacteriological study is received intraoperational. From other 48 patients bile is received by endoscopyc method during studying big duodenal papilla. The bacteriological study of the bile is revealed presence of bacteriocholia in 95,5% of examined patients. Most often were revealed Escherichia coli, Klebsiella, Pseudomonas aeruginosa. It is also noted that, at level of serum albuminum more than 99 mkm, ductular bile was infected in 100% cases, however 90,6% flora was presented only by two forms: Klebsiella and Pseudomonas aeruginosa.